2019
DOI: 10.1177/1049909118822287
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Attitudes Toward End-of-Life Care Among Medical Students: Nationwide Survey for Fourth-Year Korean Medical Students

Abstract: Background: Positive attitudes for end-of-life (EOL) care along with adequate education are key factors for the provision of quality EOL care. This national study was conducted to identify the factors that influence attitudes toward EOL care on medical students. Method: An anonymous survey was designed and administered to fourth-year medical students at all 41 medical schools in Korea. Topics related to EOL care were assessed in classroom teaching, bedside teaching, and feedback experiences during clinical cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 20 publications
2
23
0
1
Order By: Relevance
“…Our findings are consistent with reports from medical schools worldwide, which document deficits in PC and EOL education [9,10]. The study adds to the literature by providing the perceptions and intentions of medical school deans, and identifying barriers they faced in providing PC education.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings are consistent with reports from medical schools worldwide, which document deficits in PC and EOL education [9,10]. The study adds to the literature by providing the perceptions and intentions of medical school deans, and identifying barriers they faced in providing PC education.…”
Section: Discussionsupporting
confidence: 89%
“…Lecture-based teaching alone, which was reported to be the primary mode of PC teaching by our respondents, may not be as effective as direct experience in changing a student's attitude toward EOL care. Studies have shown that clinical exposure during clerkship is the most critical factor positively impacting perceptions of EOL treatment [9,10]. However, deans in our study described significant gaps in clinical exposure to PC.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In a recent study, many students had limited bedside experience and feedback from a clinical supervisor in end-of-life care (EOL) curricula; with students appearing to need more clinical experiences and feedback as these are paramount to the competencies of medical students. 19 EOL care education in Korea is yet to meet increased learning needs, and it varies greatly depending on the medical school (2-36 hours). Students feel the need for HPC education, but do not believe the current education is sufficient.…”
Section: Editorialmentioning
confidence: 99%